The Immune System Drives Synapse Loss During Lipopolysaccharide-Induced Learning and Memory Impairment in Mice - Xin, Yi-Rong; Jiang, Jun-Xing; Hu, Yang; Pan, Jun-Ping; Mi, Xiang-Nan; Gao, Qin; Xiao, Fei; Zhang, Wei; Luo, Huan-Min (Frontiers in Aging Neuroscience, 2019)
Although lipopolysaccharides (LPS) have been used to induce an Alzheimer’s disease like animal model, the exact mechanisms involved have not been studied. This study was designed to confirm an animal model of learning and memory impairment induced by LPS, and explore which biological processes and pathways have taken part in it. Mice were continuously intraperitoneally injected with LPS for 7 days. Learning and memory related behavioral and pathological performances were tested by Morris water maze and immunostaining respectively. The expressions of C1q, C3, microglia and their regulators-cytokines were comprehensively detected. After 7 days of administration, LPS induced learning and memory disorder in mice, which is attributed to neural impairment and synapse loss in hippocampus. The immune system was activated, in which classical complement pathway and microglia phagocytosis were shown to be involved in the synapse loss. LPS-injected mouse can serve as an early memory impairment model for anti-AD drugs researches.